Qualitative Characterization of Xylem Vessels of 23 Woody Trees and Shrubs in Northeastern Mexico: Its Significance - Maiti, Ratikanta; Rodríguez, Humberto González; Díaz, Jeff Christofher González (International Journal of Economic Plants, 2017)
The present study was undertaken to determine the variability of secondary xylem vessel characteristics of 23 woody trees and shrubs at Linares, Northeast Mexico. The results revealed a large variability in secondary xylem vessel characteristics. Species are grouped on the basis of vessel lengths, breadth and inclination of end walls which are considered to be related to taxonomic delimitation, evolutionary trends and adaptation of the species to xeric environment.